Contact angles and wettability of ionic liquids on polar and non-polar surfaces. Issue 47 (11th November 2015) - Pereira, Matheus M.; Kurnia, Kiki A.; Sousa, Filipa L.; Silva, Nuno J. O.; Lopes-da-Silva, José A.; Coutinho, João A. P.; Freire, Mara G.
Abstract : Experimental and theoretical approaches were combined and a new extended list for the contact angles of ionic liquids on three surfaces is provided. Abstract : Many applications involving ionic liquids (ILs) require the knowledge of their interfacial behaviour, such as wettability and adhesion. In this context, herein, two approaches were combined aiming at understanding the impact of the IL chemical structures on their wettability on both polar and non-polar surfaces, namely: (i) the experimental determination of the contact angles of a broad range of ILs (covering a wide number of anions of variable polarity, cations, and cation alkyl side chain lengths) on polar and non-polar solid substrates (glass, Al-plate, and poly-(tetrafluoroethylene) (PTFE)); and (ii) the correlation of the experimental contact angles with the cation–anion pair interaction energies generated by the Conductor-like Screening Model for Real Solvents (COSMO-RS). The combined results reveal that the hydrogen-bond basicity of ILs, and thus the IL anion, plays a major role through their wettability on both polar and non-polar surfaces. The increase of the IL hydrogen-bond accepting ability leads to an improved wettability of more polar surfaces (lower contact angles) while the opposite trend is observed on non-polar surfaces. The cation nature and alkyl side chain lengths have however a smaller impact on the wetting ability of ILs. Linear correlations were found between the experimental contact angles and the cation–anion hydrogen-bonding and cation ring energies, estimated using COSMO-RS, suggesting that these features primarily control the wetting ability of ILs. Furthermore, two-descriptor correlations are proposed here to predict the contact angles of a wide variety of ILs on glass, Al-plate, and PTFE surfaces. A new extended list is provided for the contact angles of ILs on three surfaces, which can be used as a priori information to choose appropriate ILs before a given application.